Impact of perceived organizational support on organizational citizenship behavior: the mediating roles of job insecurity and organizational trust / Hong Liang, Daisy Kee Mui Hung and Siti Rohaida Mohamad Zainal - Hong, Liang; Daisy Kee, Mui Hung; Mohamad Zainal, Siti Rohaida (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study aims to examine the impact of perceived organizational support (POS) on organizational citizenship behavior (OCB) through the mediation role of job insecurity and organizational trust. We employed the cross-sectional design with a questionnaire to collect data from 296 selected employees of manufacturing industries in Malaysia. The PLS-SEM technique is used in this study to test the proposed hypotheses. The findings reveal that POS directly impacts OCB, and this relationship is also mediated by job insecurity and organizational trust. Research on the relationship between perceived organizational support (POS) and organizational citizenship behaviour has primarily adopted a social exchange perspective. The results showed that job insecruity and organizational trust was a significant mediator of the relationship in POS and OCB. Moreover, perceived job insecurity tended to attenuate the relationship between POS and OCB, but enhanced the direct relationship between perceived organizational support and OCB. This study also filled the gap in the existing literature concerning job insecurity and organizatioanl trust of the manufacturing sector in Malaysia.Implications and future research directions are discussed.